Join now for JEE/NEET and also prepare for Boards Learn Science & Maths Concepts for JEE, NEET, CBSE @ Rs. 99! Register Now
Hey there! We receieved your request
Stay Tuned as we are going to contact you within 1 Hour
One of our academic counsellors will contact you within 1 working day.
Click to Chat
1800-5470-145
+91 7353221155
CART 0
Use Coupon: CART20 and get 20% off on all online Study Material
Welcome User
OR
LOGIN
Complete Your Registration (Step 2 of 2 )
Sit and relax as our customer representative will contact you within 1 business day
OTP to be sent to Change
Polynomial is an algebraic expression which includes constants, variables and exponents. It is the expression in which the variables have only positive integral powers.
1. 4x^{3} + 3x^{2} + x +3 is a polynomial in variable x.
2. 4x^{2} + 3x^{-1} - 4 is not a polynomial as it has negative power.
3. 3x^{3/2 }+ 2x – 3 is not a polynomial.
Polynomials are denoted by p(x), q(x) etc.
In the above polynomial 2x^{2}, 3y and 2 are the terms of the polynomial.
2 and 3 are the coefficient of the x^{2} and y respectively.
x and y are the variables.
2 is the constant term which has no variable.
If there is only one variable in the expression then this is called the polynomial in one variable.
x^{3} + x – 4 is polynomial in variable x and is denoted by p(x).
r^{2} + 2 is polynomial in variable r and is denoted by p(r).
Types of polynomials on the basis of the number of terms
Types of polynomials on the basis of the number of degrees
The highest value of the power of the variable in the polynomial is the degree of the polynomial.
If p(x) is a polynomial then the number ‘a’ will be the zero of the polynomial with p(a) = 0. We can find the zero of the polynomial by equating it to zero.
Given polynomial is p(x) = x - 4
To find the zero of the polynomial we will equate it to zero.
x - 4 = 0
x = 4
p(4) = x – 4 = 4 – 4 = 0
This shows that if we place 4 in place of x, we got the value of the polynomial as zero. So 4 is the zero of this polynomial. And also we are getting the value 4 by equating the polynomial by 0.
So 4 is the zero of the polynomial or root of the polynomial.
The root of the polynomial is basically the x-intercept of the polynomial.
If the polynomial has one root, it will intersect the x-axis at one point only and if it has two roots then it will intersect at two points and so on.
Find p (1) for the polynomial p (t) = t^{2} – t + 1
p (1) = (1)^{2} – 1 + 1
= 1 – 1 + 1
= 1
We know the property of division which follows in the basic division, i.e.
Dividend = (Divisor × Quotient) + Remainder
This same follows the division of polynomial.
If p(x) and g(x) are two polynomials in which the degree of p(x) ≥ degree of g(x) and g(x) ≠ 0 are given then we can get the q(x) and r(x) so that:
P(x) = g(x) q(x) + r(x),
where r(x) = 0 or degree of r(x) < degree of g(x).
It says that p(x) divided by g(x), gives q(x) as quotient and r(x) as remainder.
Let’s understand it with an example
We can see that ‘x’ is common in the above polynomial, so we can write it as
Hence 3x^{2 }+ x + 1 and x the factors of 3x^{3} + x^{2} + x.
Divide x^{2} - 3x -10 by 2 + x
Step 1: Write the dividend and divisor in the descending order i.e. in the standard form. x^{2} - 3x -10 and x + 2
Divide the first term of the dividend with the first term of the divisor.
x^{2}/x = x this will be the first term of the quotient.
Step 2: Now multiply the divisor with this term of the quotient and subtract it from the dividend.
Step 3: Now the remainder is our new dividend so we will repeat the process again by dividing the dividend with the divisor.
Step 4: – (5x/x) = – 5
Step 5:
The remainder is zero.
Hence x^{2} - 3x – 10 = (x + 2)(x - 5) + 0
Remainder Theorem says that if p(x) is any polynomial of degree greater than or equal to one and let ‘t’ be any real number and p (x) is divided by the linear polynomial x – t, then the remainder is p(t).
As we know that
P(x) = g(x) q(x) + r(x)
If p(x) is divided by (x-t) then
If x = t
P (t) = (t - t).q (t) + r = 0
To find the remainder or to check the multiple of the polynomial we can use the remainder theorem.
What is the remainder if a^{4} + a^{3} – 2a^{2} + a + 1 is divided by a – 1.
P(x) = a^{4} + a^{3} – 2a^{2} + a + 1
To find the zero of the (a – 1) we need to equate it to zero.
a -1 = 0
a = 1
p (1) = (1)^{4} + (1)^{3} – 2(1)^{2} + (1) + 1
= 1 + 1 – 2 + 1 + 1
= 2
So by using the remainder theorem, we can easily find the remainder after the division of polynomial.
Factor theorem says that if p(y) is a polynomial with degree n≥1 and t is a real number, then
(y - t) is a factor of p(y), if p(t) = 0, and
P (t) = 0 if (y – t) is a factor of p(y).
Check whether g(x) = x – 3 is the factor of p(x) = x^{3 }- 4x^{2 }+ x + 6 using factor theorem.
According to the factor theorem if x - 3 is the factor of p(x) then p(3) = 0, as the root of x – 3 is 3.
P (3) = (3)^{3 }- 4(3)^{2} + (3) + 6
= 27 – 36 + 3 + 6 = 0
Hence, g(x) is the factor of p(x).
Find the value of k, if x – 1 is a factor of p(x) = kx^{2 }– √2x + 1
As x -1 is the factor so p(1) = 0
Factorization can be done by three methods
1. By taking out the common factor
If we have to factorize x^{2} –x then we can do it by taking x common.
x(x – 1) so that x and x-1 are the factors of x^{2} – x.
2. By grouping
ab + bc + ax + cx = (ab + bc) + (ax + cx)
= b(a + c) + x(a + c)
= (a + c)(b + x)
3. By splitting the middle term
x^{2} + bx + c = x^{2} + (p + q) + pq
= (x + p)(x + q)
This shows that we have to split the middle term in such a way that the sum of the two terms is equal to ‘b’ and the product is equal to ‘c’.
Factorize 6x^{2} + 17x + 5 by splitting the middle term.
If we can find two numbers p and q such that p + q = 17 and pq = 6 × 5 = 30, then we can get the factors.
Some of the factors of 30 are 1 and 30, 2 and 15, 3 and 10, 5 and 6, out of which 2 and 15 is the pair which gives p + q = 17.
6x^{2} + 17x + 5 =6 x^{2} + (2 + 15) x + 5
= 6 x^{2} + 2x + 15x + 5
= 2 x (3x + 1) + 5(3x + 1)
= (3x + 1) (2x + 5)
Factorize 8x^{3} + 27y^{3} + 36x^{2}y + 54xy^{2}
The given expression can be written as
= (2x)^{3 }+ (3y)^{3} + 3(4x^{2}) (3y) + 3(2x) (9y^{2})
= (2x)^{3} + (3y)^{3} + 3(2x)^{2}(3y) + 3(2x)(3y)^{2}
= (2x + 3y)^{3} (Using Identity VI)
= (2x + 3y) (2x + 3y) (2x + 3y) are the factors.
Factorize 4x^{2} + y^{2} + z^{2} – 4xy – 2yz + 4xz.
4x^{2} + y^{2} + z^{2} – 4xy – 2yz + 4xz = (2x)^{2 }+ (–y)^{2} + (z)^{2} + 2(2x) (-y)+ 2(–y)(z) + 2(2x)(z)
= [2x + (- y) + z]^{2} (Using Identity V)
= (2x – y + z)^{2} = (2x – y + z) (2x – y + z)
Get your questions answered by the expert for free
You will get reply from our expert in sometime.
We will notify you when Our expert answers your question. To View your Question
Revision Notes on Probability Probability...
Revision Notes on Areas of Parallelograms and...
Revision Notes on Statistics Statistics Statistics...
Revision Notes on Number Systems Introduction to...
Revision Notes on Coordinate Geometry Cartesian...
Revision Notes on Lines and Angles Basic terms and...
Revision Notes on Circles Introduction to Circles...
Revision Notes on Triangles Triangle A closed...
Revision Notes on Constructions Introduction to...
Revision Notes on Quadrilaterals Quadrilateral Any...
Revision Notes on Linear Equations in Two...
Revision Notes on Surface Areas and Volumes Plane...
Revision Notes on Introduction to Euclid’s...
Revision Notes on Heron’s Formula Perimeter...